RANCANGAN BUKU PENGAYAAN PENGETAHUAN "KONSEP FISIKA PETIR" - Rugun Ivania Laudes; Desnita Desnita; A. Handjoko Permana (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This research aims to develop knowledge enrichment books eligible to static electricity based on competence 3.5 grade XII, that is analize the electrical force, a strong electric field, flux, electric potential, electric potential energy and its application in various cases of static. Eligibility is measured using four indicators that have been established by Pusat Kurikulum dan Perbukuan (PUSKURBUK) namely;content, presentation,language, and graphic. The method applied is the development of research which refers to of Dick & Carey. Survey has done to know the necessity of enrichment book inschools in Jakarta, famous book stores in Jakarta , and Pusat Kurikulum dan Perbukuan, the results is just a few books about lightning but only as part of a science popular, not discuss the specifics of the concept of physics. Referring to the results of a survey and quality standards enrichment books, written draft of the book enrichment "Concepts of Physics Lightning" with a communicative language and comes with the presentation of an image that makes it easy to understand explanation of the concept of physics. Keywords: knowledge enrichment book, Lightning, Static electricity